Impact of COVID-19 mandatory lockdown on maternal gestational weight gain and neonatal macrosomia rate at an academic medical center in Israel. (31st December 2023) - Benyamini Raischer, Hedi; Garmi, Gali; Malchi, Daniel; Nachshon, Avinoam A.; Inbar, Shiri; Romano, Shabtai; Salim, Raed
Abstract: Background: In an effort to prevent the spread of coronavirus disease 2019 (COVID-19), governments restricted outdoor activities and imposed lockdown quarantine. This change in lifestyle probably affected individuals' eating habits and physical activity. Objective: To examine the effect of lockdown due to the COVID-19 pandemic on maternal antenatal weight gain, neonatal macrosomia, and other maternal and neonatal outcomes of women delivering at an academic medical center in Israel. Method: A retrospective, two-period cohort study conducted at a university teaching medical center in Afula, Israel. The study period was between April and September 2020. This period signifies worsening in pandemic situations, during which citizens experienced strict prolonged lockdown measures. The parallel unexposed period (control period) was between April and September 2019. Singleton pregnancies delivered at >24 weeks were eligible. Primary outcome was incidence of macrosomia. Secondary outcomes included gestational weight gain, body mass index (BMI) at delivery, rates of gestational diabetes mellitus (GDM), mode of delivery, postpartum hemorrhage (PPH), and neonatal outcomes reflecting neonatal birth weight and condition at delivery. Results: A total of 4, 765 women were included, 2, 442 in the study group and 2, 323 in the control group. The incidence of macrosomia was significantly higher in 2020 (6.2%) than in 2019 (4.9%), ( p = .048; OR: 1.29; 95% CI: 1.002– 1.65). Women gained significantly more weight (median 1 kg more), weighed more at delivery (median 1 kg), and had higher BMI at delivery in 2020 compared with those in 2019 ( p < .01). The incidence of GDM was 9.5% and 8.5% in the study and control groups respectively ( p = .26; OR: 1.12; 95% CI: 0.92–1.37). Greater percentage of women did not perform the glucose challenge test in 2020 (9.9%) compared with those in 2019 (7.5%) ( p = .003, OR: 1.36; 95% CI: 1.11–1.67). The incidence of any hypertension related to pregnancy was significantly higher in 2020 compared to 2019 (5.8% vs 4.4% respectively, ( p = .042; OR: 1.32; 95% CI: 1.02–1.71). The proportion of women who smoked during pregnancy was also significantly higher in 2020 than in 2019 (5.1% vs 3.7%, respectively, p = .02; OR: 1.40; 95% CI: 1.06–1.86). Delivery mode did not differ, while the incidence of PPH was significantly higher in 2020 than in 2019 (5.6% vs 3.4%, respectively, p = .001; OR: 1.65; 95% CI: 1.25–2.19). Neonatal condition at delivery was comparable. Conclusion: COVID-19-related lockdown was associated with the increased rate of macrosomic infants. This indirect effect of the pandemic is probably related to poorer maternal antenatal metabolic health status. Long-term consequences should be further examined.